Investigation Status of Heat Exchange while Boiling Hydrocarbon Fuel - D. S. Obukhov (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика)
The paper contains analysis of heat exchange investigations while boiling hydrocarbon fuel. The obtained data are within the limits of the S.S. Kutateladze dependence proposed in 1939. Heat exchange at non-stationary heat release has not been investigated. The data for hydrocarbon fuel with respect to critical density of heat flow are not available even for stationary conditions.